KEWAJIBAN PENCATATAN PERKAWINAN DI INDONESIA PERSPEKTIF HUKUM ISLAM - Muhammad; M. Fahmi Al-Amruzi; Akhmad Sukris Sarmadi (Tarbawi, 2026)
Marriage registration is one of the legal provisions in Indonesia regulated in Law No. 1 of 1974, Article 1 concerning Marriage. The status of the legal provisions for those registration is mentioned by legal experts as something that must be carried out for married couples without exception. The main purpose of this registration is not only to provide legal certainty for married couples and children born from the marriage, but it is also important to prevent unwanted occurrences when carrying out the marriage covenant, including wath syubhat and even adultery. In the context of Islamic law, a valid marriage is generally considered for the marriage pillar determined by sharia. In earlier Islamic practice, this also had its own way, one of which was with witnesses and walimah. Marriage registration has become important to avoid legal problems that may arise later on through verification. This regulation even more important than muamalah because of its systematic impact. The methodology I use is qualitative method and normative method to analyze the legal basis from the perspective of Qiyas Aulawi theory and Maqasid al-Shariah. This article shows this registration is not only important for legal certainty, is in accordance with the principles in Islamic law that promote maslahah and the protection of individual rights.